Time-Series Analysis of Malaria Cases Among Suspected Febrile Patients Attending a Peri-Rural Health Centre Between February 2020- January 2021 - Adekola, Hafeez Aderinsayo; Egberongbe, Haneefat Olabimpe; Olanrewaju, Michael; Onajobi, Ismail B; Samson, Oyindamola John; Kareem, Wahab Ademola (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
Sub-Saharan Africa has a high rate of malaria-related morbidity and death, with Nigeria accounting for a substantial proportion of these cases owing to its malarious nature. Most Nigerians live in environments that encourage the development of mosquito vectors that are responsible for malaria transmission. This study aimed to determine the prevalence of malaria in the peri-urban areas. A time-series analysis was performed on 1,141 people with suspected febrile illness who visited a peri-urban health center over the course of a year (February 2020 – January 2021). Each person who presented to the hospital and was tested for malaria was included in the study. The 12-month study reported an overall prevalence of 24% (p<0.05). A total of 273 individuals were found to be seropositive, with males (162) having a higher prevalence than females (111). Cases of seropositivity have been reported in all age groups. This study concluded that malaria remains a public health concern in the country, particularly in areas favorable for mosquito vector reproduction. Consequently, elimination approaches should be strengthened to safeguard people, particularly in vulnerable regions.